Comparative study on different coupling agents used as surfactants: effect on dispersion properties of TiN nanoparticles. (1st July 2014) - Cheng, Guojun; Qian, Jiasheng; Xia, Ru; Chen, Peng; Miao, Jibin; Yang, Bin
Abstract : Γ‐methacryloxypropyl trimethoxy silane (KH‐570) and macromolecular coupling agents (MCA) (St/AN/KH‐570 random copolymer) were used as surfactants for the surface modification of titanium nitride (TiN) nanoparticles (nanoTiN). The structure and dispersion properties of the modified nanoTiN were investigated by Fourier transform infrared (FTIR) spectra, X‐ray photoelectron spectroscopy (XPS), a sedimentation stability experiment (SSE), a contact angle measuring instrument (CAMI) and a high‐resolution transmission electron micrograph (HRTEM). According to the spectra of FTIR and XPS, it can be inferred that the KH‐570 and MCA covalently bonded on the surface of nanoTiN and an organic coating layer was formed. The SSE and the CAMI showed that the stable dispersion and the hydrophobic property were improved significantly. The results of the HRTEM showed that the surfactants improved the dispersibility of particles in the organic solution and the SBR matrix. It is found that the MCA can more effectively improve the dispersion stability of nanoTiN because of a more strong steric stabilisation of the macromolecular structure, which facilitated to hinder the aggregation of nanoparticles.